Triazoles and strobilurins for the management of turmeric leaf spot - Adipathi, P; Kumar, P Rajesh; Rajesha, G; Nakkeeran, S (Indian Journal of Plant Protection, 2020)
In vitro, greenhouse and field experiments were conducted to evaluate the efficacy of triazoles and strobilurins group of fungicides at different concentrations to manage turmeric leafspot caused by Colletotrichum capsici. Among these fungicides, propiconazole (25%SC) and tebuconazole + trifloxystrobin (50:25%WG) were individually effective against C. capsici even at the lowest concentration of 10 μg ml-1 by completely (100%) inhibiting its mycelial growth and mycelial biomass. Tebuconazole + trifloxystrobin (50:25%) WG showed the highest level of sporulation inhibition, recorded 0.3 x 106 ml-1 conidial density, followed by propiconazole (2.0 x 106 ml-1) 10 μg ml-1 concentration as compared to control (25.6 x 106 ml-1). Foliar spraying of propiconazole @ 1 ml-1 significantly reduced leaf spot disease, which recorded 11.8 per cent disease index (PDI) in trial-I and 16.8 PDI in trial-II, whereas in control it was 54.5 and 59.50 PDI, respectively under glass house condition. Two applications of propiconazole at 1 ml-1 concentration revealed the least PDI of 13.5% followed by tebuconazole + trifloxystrobin (1 ml-1), which recorded 14.3% under field condition, whereas in control recorded 57.5% and 53.5%, respectively in trial-I and trial II. The maximum rhizome yield was recorded as 28.8 t/ha in trial-I and 25.4 t/ha in trial-II against the control, which recorded 19.8 and 17.5 t/ha, respectively. Propiconazole and tebuconazole + trifloxystrobin were found to be highly effective fungicides for the management of turmeric leaf spot.